Developing cognitive behaviour therapy training in India: Using the Kolb learning cycle to address challenges in applying transcultural models of mental health and mental health training. (October 2014) - Beck, Andrew; Virudhagirinathan, B. S.; Santosham, Sangita; Begum, Faiz Jahan
Abstract Although mental health workers in India across all major professional groups have identified an unmet need for training in cognitive behaviour therapy (CBT), the uncritical export of models of mental health, therapy provision and training to low- and middle-income countries is a problematic process. This paper describes the context for the first stand-alone CBT training programme in India, based in Chennai. This paper includes an evaluation of the first phase of the training and information from trainees regarding the quality and applicability of the training to their working context. The paper provides an overview of some of the critiques that are pertinent to this process and considers the way that the Kolb learning cycle can be used as a framework within training to go some way to addressing these difficulties.